INTANGIBLE ASSETS, NILAI PERUSAHAAN, DAN KINERJA KEUANGAN - ADI ERAWATI, NI MADE; SUDANA, I PUTU (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 4 No 1 (2009), 2009)
This paper is intended to discuss the theory of intangible asset and its roles to firm’s value and its financial performance. The main premise to discuss is that intangible asset, along with tangible assets, determine the firm’s value and its performance. If a tree falls in the forest, does it make a sound? That's a classic question for philosophical pondering. How about this one: If an asset is intangible, does it make an impact on the corporate bottom line? Of course it does. But how can this impact be captured, quantified or valued in the financial analysis? Businesses exist to create and render value to its stakeholders. The four aspects in value creating dimension matrix become determinants for the companies’ ability. The main contributor for that ability lies on the specific asset called intangible asset. For that reason, users of firms’ financial statements should have opportunities to search for firms’ information related to its intellectual assets. Lack of objectivity, in determining the value of intangible asset, should not be judged as the excuse not to presenting this important and relevant information to the users.
Keywords: value creation, intangible asset, firm’s value, financial performance.